Validation of the Barthel Index in Chinese nursing home residents: an item response theory analysis - Liang, Minyu; Yin, Mei; Guo, Bing; Pan, Yichao; Zhong, Tong; Wu, Jieyi; Ye, Zengjie (Frontiers in Psychology, 2024)
Background: The Barthel Index (BI) has been implemented to standardized grading assessments for clinical needs, insurance support, and long-term care resource allocation in China. But its psychometric properties among nursing home residents remain unclear. Therefore, this study aims to assess and modify the psychometric properties of BI in nursing home residents.Methods: A total of 1402 individuals residing undergoing evaluation process in a nursing home facility in China were included in this study from November 2021 to November 2022. Correlations between items were examined to identify potential multicollinearity concerns. Unidimensional item response theory (IRT) was used to validate and modify the single structure of BI. Furthermore, the logistic regression/IRT hybrid DIF detection method was conduct to assess differential item functioning (DIF) between dementia group and normal group.Results: The pairing of items 5 ("bowl control") and 6 ("bladder control") revealed a local dependence issue, leading to their consolidation. Items 56 (bowel and bladder control) and 9 (mobility) both displayed poor fit and underwent category collapsing. Through the application of the generalized partial credit model, the adjusted scale displayed better fit indices, demonstrating robust discriminative power (DC >1.5) and orderly thresholds. Furthermore, non-uniform DIF was identified in item 2 (bathing) between the dementia and normal groups.Conclusions: The modified BI demonstrated favorable psychometric properties and proved to be suitable for evaluating nursing home residents experiencing moderate functional impairment, which may provide precise evaluation for long-term care resource allocation. Future studies could explore the integration of supplementary measurements, such as objective indices to assess a broader spectrum of functional statuses to potentially enhance the limited precision width observed in BI.删除了: As the ageing population grows, there is a growing need for 54 standardised evaluations to assess older adults for clinical needs, 55 insurance support, and long-term care resource allocation. Although t 56